2012
DOI: 10.1590/s0066-782x2012005000106
|View full text |Cite
|
Sign up to set email alerts
|

Fibrilação atrial e demência: resultados do São Paulo ageing & health study

Abstract: Background: Atrial fibrillation (AF) is a controversial risk factor for dementia.Objective: The objective of this study was to assess the association between AF and dementia in the "Sao Paulo Ageing & Health" (SPAH) study participants.Methods: SPAH is a cross-sectional, population-based study of elderly people living in a deprived neighborhood in Sao Paulo, Brazil. Dementia diagnosis was performed according to the 10/66 study group protocol based on Diagnostic and Statistical Manual of Mental Disorders (DSM-IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
15
0
5
Order By: Relevance
“…The association between dementia and some racial and ethnic groups has been confirmed in some earlier reports [88][89][90]. Most studies have been conducted in European countries such as Italy [10,23,25,33,35], Sweden [11,30], the Netherlands [21,44], the United Kingdom [22,26,50,91], Finland [12,27], France [28], Germany [29], or American countries [13,14,18,19,39,40,46,[92][93][94]; while Taiwan [43], Singapore [51], and China [52] were the only Asian countries wherein such investigations have been carried out.…”
Section: Different Study Settings and Designsmentioning
confidence: 64%
See 1 more Smart Citation
“…The association between dementia and some racial and ethnic groups has been confirmed in some earlier reports [88][89][90]. Most studies have been conducted in European countries such as Italy [10,23,25,33,35], Sweden [11,30], the Netherlands [21,44], the United Kingdom [22,26,50,91], Finland [12,27], France [28], Germany [29], or American countries [13,14,18,19,39,40,46,[92][93][94]; while Taiwan [43], Singapore [51], and China [52] were the only Asian countries wherein such investigations have been carried out.…”
Section: Different Study Settings and Designsmentioning
confidence: 64%
“…Furthermore, the diagnostic method used to confirm AF was yet another important means to justify different results. For instance, some studies used ICD codes [13,30,36,37,40,43,50], while others employed electrocardiography (ECG) [13,21,22,26,27,33,[38][39][40]45,49,50], medical history, notes [10,12,13,22,25,28,30,33,34,38,42,45,49,50], and physical examinations alone or in combination with other techniques [12,25,30,49]. In addition, in some studies, no Figure 2 Worldwide distribution of national studies investigating association between atrial fibrillation and cognitive function.…”
Section: Different Study Settings and Designsmentioning
confidence: 99%
“…For example, Americans of either Hispanic ethnicity or African‐American race appear to have higher stroke risks, despite a lower prevalence of AF relative to white individuals . Asians with AF may have particularly high risks for stroke, potentially due to variations in both anticoagulant prescribing practices and variable genetic‐based responses to anticoagulation with warfarin . Similar variation in thromboembolism risk and outcomes may also occur in other regions, but comprehensive global assessments of thromboembolism outcomes, particularly in developing countries, are lacking.…”
Section: Associations Between Af and Mortality Morbidity And Qualitmentioning
confidence: 99%
“…A meta‐analysis of 21 studies found decreased cognitive scores associated with AF in different populations . In Brazil, AF patients were 2.8 times more likely to have dementia, relative to those without AF . AF also is associated with chronic kidney disease.…”
Section: Associations Between Af and Mortality Morbidity And Qualitmentioning
confidence: 99%
See 1 more Smart Citation